SPE Western Regional Meeting 2010
DOI: 10.2118/132372-ms
|View full text |Cite
|
Sign up to set email alerts
|

Review of Cuttings Transport in Directional Well Drilling: Systematic Approach

Abstract: Hole cleaning during directional well drilling is a major concern in the oil patch and must be monitored and properly controlled during the entire drilling operation. Inadequate drilled cuttings removal can cause many costly problems such as mechanical pipe sticking, excessive torque and drag, difficulties in casing/cementing and in logging. Low fluid annular velocity, lack of drill pipe rotation and the wrong mud properties are primary factors in the inadequacy of effective hole cleaning. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Previous studies indicate that cuttings transport is influenced by many factors, such as cuttings characteristics, drilling fluid type and rheology, operational parameters including drill pipe rotation, pump rate, weight on bit, ROP, eccentricity and diameter of hole and drill pipe, and wellbore inclination (Okrajni and Azar, 1986;Sifferman and Becker, 1992;Zeidler, 1972). A comprehensive review of cuttings transport studies was reported by Kelin et al (2013) and Nazari et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that cuttings transport is influenced by many factors, such as cuttings characteristics, drilling fluid type and rheology, operational parameters including drill pipe rotation, pump rate, weight on bit, ROP, eccentricity and diameter of hole and drill pipe, and wellbore inclination (Okrajni and Azar, 1986;Sifferman and Becker, 1992;Zeidler, 1972). A comprehensive review of cuttings transport studies was reported by Kelin et al (2013) and Nazari et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mud type has small to moderate positive effect on cuttings removal away from PDC bit [18]. Different mud types lead to different bed consolidation.…”
Section: Mud Rheologymentioning
confidence: 97%
“…Nazari [10] found that there are several drilling variables that affect cutting transport in directional wells. These variables are the following: …”
Section: Basics Of Cutting Transportmentioning
confidence: 99%